Organización Contable a la Empresa “Comercial Credillantas MC” de la Ciudad de Loja, Periodo Abril – Junio de 2024. - César David, Parra Sarango (2025)
This research project titled "Accounting Organization for Credillantas MC in Loja: April - June 2024", has been developed in accordance with the regulations of the Universidad Nacional de Loja, Alma Mater. It is designed to meet the requirements for the Bachelor's Degree in Accounting and Auditing. The project began with the collection of data to create the initial inventory and the Initial Balance Sheet. Subsequently, transactions for the period from April to June 2024 are recorded. Additionally, the project involved designing and structuring subsidiary ledgers for purchases, sales, accounts receivable, and accounts payable. Finally, entries are posted, and a trial balance, work sheet, and financial statements are prepared. This study provides an administrative and financial resource for Credillantas MC in Loja. Specifically, the resulting financial statements will enable Engr. Alexandra Cartuche, the owner of Credillantas MC, to make well-informed decisions. By using key financial reports, such as the Income Statement, Balance Sheet, and Cash Flow Statement, she will be able to rely on detailed financial information.